Inductor design for a buck boost converter - Yeo, Yee Jie (Nanyang Technological University, 2024)
This paper examines the design and optimization of an inductor for a buck-boost converter, focusing on the selection of toroid types, the determination of the number of turns, and the use of multiple cores to increase performance. The study begins with an overview of toroid materials, including ferrite, iron powder and nanocrystalline, and examines their magnetic properties and suitability for high frequency applications. The effects of these materials on core loss, saturation flux density and thermal management are analyzed.